Comparison of coagulant-induced changes in isoflavone content, and texture profile of Himalayan black soybean-based tofu - Sofiya Anjum; Vasudha Agnihotri; Vasudha Agnihotri; Smita Rana (Frontiers in Sustainable Food Systems)
IntroductionThis research examined the isoflavone levels and texture characteristics of tofu produced from Himalayan black soybean, utilizing two distinct soymilk processing techniques and both synthetic and natural coagulants.MethodSoymilk was prepared following two different methos and then it was coagulated using 10 different coagulants (natural and synthetic).ResultsThe tofu made with Rhododendron arboreum floral juice exhibited the highest isoflavone levels, irrespective of the method used to prepare the soymilk. The texture quality was consistently good for tofu made with acetic acid, regardless of the soymilk preparation technique employed.DiscussionThe findings indicate that the isoflavone composition of the final product is affected by both the coagulant and the preparation techniques, with β-glucosides being more common than aglycones. The observation that the okara fraction contains a higher concentration of aglycones supports the notion that these compounds are less soluble in water and may be lost during the tofu production process. The interaction between coagulants and soymilk proteins affects tofu's texture. Upon heating, proteins unfold, exposing negatively charged disulfides that counteract the coagulants, resulting in protein aggregation. These results were further validated through factor and cluster analysis. Research has explored the effects of different coagulants and processing methods on tofu texture, including the use of natural coagulants to improve texture and flavor.